1995
DOI: 10.1002/tea.3660320509
|View full text |Cite
|
Sign up to set email alerts
|

Students' conceptions of natural selection and its role in evolution: Cases of replication and comparison

Abstract: The work of Bishop and Anderson (1990) plays a major role in educators' understanding of evolution education. Their findings remind us that the majority of university students do not understand the process of evolution but that conceptual change instruction can be moderately effective in promoting the construction of a scientific understanding. The present article details two studies that represent an effort to focus on and define the limits of the Bishop and Anderson (1990) study. Study A describes a close re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
2
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(97 citation statements)
references
References 12 publications
3
83
2
9
Order By: Relevance
“…But as decades of research in scientific education suggest, teleological thinking is one of the primary obstacles in students' path to acquiring an adequate understanding of natural selection (see Galli andMeinardi, 2011 andKelemen, 2012 for an overview). For instance, students tend to think that a "personified "Mother Nature" responded to animals functional needs by generating or conferring the functional part with a view to preserving the animal's survival" (Kelemen, 2012, p. 4; see also Kampourakis & Zogza, 2008;Moore et al, 2002;and Gregory, 2009), such as by stretching a giraffe's neck so it could reach leaves on trees (e.g., Clough & Wood-Robinson, 1985;Demastes, Settlage, & Good, 1995;Evans et al, 2010;Jensen & Finley,1995;Kampourakis and Zogza, 2008). Summing up a range of this work, Kelemen (2012) suggests that people's teleological views are "embedded within a framework of intuitions characterizing Nature as a designing agent" (p. 6).…”
Section: Benighted Teleologymentioning
confidence: 99%
“…But as decades of research in scientific education suggest, teleological thinking is one of the primary obstacles in students' path to acquiring an adequate understanding of natural selection (see Galli andMeinardi, 2011 andKelemen, 2012 for an overview). For instance, students tend to think that a "personified "Mother Nature" responded to animals functional needs by generating or conferring the functional part with a view to preserving the animal's survival" (Kelemen, 2012, p. 4; see also Kampourakis & Zogza, 2008;Moore et al, 2002;and Gregory, 2009), such as by stretching a giraffe's neck so it could reach leaves on trees (e.g., Clough & Wood-Robinson, 1985;Demastes, Settlage, & Good, 1995;Evans et al, 2010;Jensen & Finley,1995;Kampourakis and Zogza, 2008). Summing up a range of this work, Kelemen (2012) suggests that people's teleological views are "embedded within a framework of intuitions characterizing Nature as a designing agent" (p. 6).…”
Section: Benighted Teleologymentioning
confidence: 99%
“…However, efforts to develop new pedagogical tools for teaching evolutionary biology have achieved some success. Bishop and Anderson (1990) found moderate improvement in undergraduate student understanding of natural selection after intervention with a unit on that subject designed to dispel misconceptions, while Demastes et al (1995) found minimal improvement using the same instructional methods. However, high school students showed greater gains, perhaps due to differences in the presentation of instructional materials.…”
Section: Introductionmentioning
confidence: 98%
“…It is, therefore, imperative to identify the source of student confusions about evolution and to develop effective teaching tools that can correct them (National Research Council 1996;Novak 2002;Modell et al 2005;Wescott and Cunningham 2005). Although cultural and political viewpoints affect student understanding (Almquist and Cronin 1988;Sinclair et al 1997;Hokayem and BouJaoude 2008), even students who claim to accept evolutionary theory often demonstrate little understanding of its basic principles (e.g., Bishop and Anderson 1990;Demastes et al 1995). These misunderstandings are instead often directly linked to students having their own incorrect conception of the functioning of the world (known as misconceptions), which prevents them from being able to use scientifically accepted concepts in thinking through some scientific problems (Greene 1990;Ferrari and Chi 1998; but see Hamza and Wickman 2008).…”
Section: Introductionmentioning
confidence: 99%
“…age of pupils, teaching time and content of lessons. Bearing this in mind, it is noted that, in general, the improvement in results reported has not matched ours (Bishop & Anderson, 1990;Bizzo, 1994, Demastes, Settlage & Good, 1995. Good long-term retention was achieved in a study by Jiménez-Aleixandre (1992).…”
Section: Methodological Issuesmentioning
confidence: 67%